2015
DOI: 10.1111/ijd.12884
|View full text |Cite
|
Sign up to set email alerts
|

Four cases of mucous membrane pemphigoid with clinical features of oral lichen planus

Abstract: Because MMP and OLP require different treatments, all dentists and dermatologists should have knowledge about the disease entity and the serological diagnostic methods for various types of MMP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…Thus, given the often innocuous clinical appearance of oral LPP that resembles oral LP, as noted in our own clinical experiences as well as that of Fukuda et al , we would like to emphasize the importance of immunofluorescence studies to establish a diagnosis of LPP to ensure a prompt referral to the appropriate specialists to prevent debilitating sequelae secondary to mucosal scarring.…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…Thus, given the often innocuous clinical appearance of oral LPP that resembles oral LP, as noted in our own clinical experiences as well as that of Fukuda et al , we would like to emphasize the importance of immunofluorescence studies to establish a diagnosis of LPP to ensure a prompt referral to the appropriate specialists to prevent debilitating sequelae secondary to mucosal scarring.…”
mentioning
confidence: 73%
“…Contributing to its lack of recognition, oral LPP is likely frequently underdiagnosed due to the lack of prescribed immunofluorescence studies in cases that may appear similar to oral LP. Including the recently published findings of Fukuda and colleagues, there are now 35 reported cases of LPP with well‐characterized oral involvement that have undergone confirmatory testing with direct immunofluorescence, 31 (89%) of which presented clinically with classic reticular or erosive LP with an absence of intraoral bullae . While we recognize that oral lesions of both diseases are treated in a similar manner, the utility of immunofluorescence studies in establishing the diagnosis of oral LPP is of importance, as LPP is considered a systemic autoimmune disease within the pemphigoid family that may present with a scarring phenotype affecting the conjunctivae, larynx, and/or esophagus, which carries a risk of progression to complications such as blindness, respiratory distress, and dysphagia, respectively …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, indirect and direct immunofl uorescence have emerged as tools that can be used in conjunction with histopathology in making these diffi cult diagnoses (5). It is important to consider oral LABD as a diff erential in cases of clinically suspected oral lichen planus, especially those that fail to respond to initial therapies.…”
Section: Discussionmentioning
confidence: 99%
“…We read the recent article by Fukuda et al with great enthusiasm. In this article the authors reported the oral lichen planus (OLP)‐like presentation of mucous membrane pemphigoid (MMP).…”
mentioning
confidence: 99%